The Role of Interleukin 1β, Fibroblast Growth Factor, Fibroblasts, Keratinocytes, Granulation Tissue and Collagen Density in the Wound Healing Phase (Study of Wound Healing in the Inflammation, Proliferation, and Remodeling Phases) - Christanto, Antonius; Cilmiaty, Risya; Setiamika, Made; Yudhani, Ratih Dewi; Dirgahayu, Paramasari; Pamungkasari, Eti Poncorini; Nurwati, Ida (Biocaster : Jurnal Kajian Biologi, 2025)
This scoping review explores the roles of interleukin 1β, fibroblast growth factor, fibroblasts, keratinocytes, granulation tissue, and collagen density in the wound healing process, focusing on inflammation, proliferation, and remodeling phases. A systematic literature search identified studies investigating molecular and cellular mechanisms involved in wound repair. Findings reveal that fibroblast-derived exosomes carrying miR-93-5p inhibit autophagy, delaying diabetic wound healing. Controlled growth factor delivery enhances angiogenesis, fibroblast proliferation, and collagen deposition, accelerating tissue regeneration. SPRR1B+ keratinocytes facilitate rapid re-epithelialization, while granulation tissue provides essential scaffolding for cell migration and neovascularization. Elevated IL-1β impairs healing by increasing matrix metalloproteinases, degrading collagen. Natural compounds like red fruit oil and Binahong leaf extract promote angiogenesis and collagen synthesis. Genetic variations in inflammatory cytokines influence healing outcomes, indicating potential for personalized therapies. This review consolidates current evidence, providing insights into cellular and molecular interactions critical for effective wound repair and guiding future regenerative medicine strategies.